Analisis Komparatif Reaksi Abnormal Return, Cummulative Abnormal Return, dan Trading Volume Activity Sebelum dan Sesudah Trend NFT di Indonesia - Ni Kadek Suantari; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2022)
This study aimed at determining the difference in the average of abnormal return, cummulative abnormal return and trading volume activity before and after NFT trends in Indonesia. The type of data used in this study was secondary data employing the data collection technique of documentation method. The determination of samples in this study employed a purposive sampling method through certain criteria so as to obtain 79 samples. The analysis techniques employed in this study were paired sample t-test and Wilxocon signed rank with the observation period of 10 days. The results of this study indicated that: (1) There was no average difference in the abnormal return before and NFT trends in Indonesia. (2) There was no average difference in the cummulative abnormal return before and after NFT trends in Indonesia. (3) There was an average difference on trading volume activity before and after NFT trends in Indonesia.